HIGH INHERITANCE ELONGATE STROMATOLITIC MOUNDS FROM THE TRANSVAAL DOLOMITE - Eriksson, K. A.; Truswell, J. F. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1973)
Elongate mound·like structures up to 10 metres across and 40 metres in length are described. Characteristic features of the mounds are their high inheritance and considerable relief which, along with the absence of sub-aerial exposure features, the fine-grained nature of the carbonate, and their vertical persistence, are taken to suggest a subtidal origin. Marine currents are considered adequate to account for their elongation.